The relationship between metacognitive strategies with academic Engagement according to the mediating role of achievement goals in students - Alkkhi, Amer Abdulkareem Salem; Sajjadian, Ilnaz; Al-Hashmy, Rasheed Nassir Khalifa; Manshaee, Gholamreza (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to investigate the relationship between metacognitive strategies and academic engagement, considering the mediating role of achievement goals and gender moderation in students.Methods and Materials: The descriptive research method was correlation type. The statistical population included all the students of Maysan University in Iraq in the 2023-2024 academic year, and 300 of them were selected by available sampling and responded to research tools including School Engagement Scale (Fredericks & Blumenfeld, 2004), the State Metacognition Invertory (O'Neill and Abedi, 1996), and Achievement Goals Questionnaire (Elliott and McGregor, 1988). Data were analyzed using Pearson's correlation coefficient and structural equation modeling and SPSS26 and PLS 3.2.8 software.Findings: The results of the path analysis test showed that metacognitive strategies did not have a significant direct relationship with academic engagement. Still, indirectly and through the mediation of achievement goals, they had an effect on academic engagement, in such a way that Orientational progress goals led to an increase in academic engagement, and avoidance achievement goals led to a decrease in academic enthusiasm. Also, gender played a moderating role in the relationship between metacognitive strategies and academic engagement.Conclusion: According to the results of this study, teaching metacognitive strategies can increase students' academic engagement through a positive impact on their achievement goals.